Effect of the abrasive grit size on the wear behavior of ceramic coatings during a micro-abrasion test - Korkut, Mehmet Hor?k; Küçük, Yilmaz; Karaoglanli, Abdulllah Cahit; Erdodan, Azmi; Er, Yusuf; Gök, Mustafa Sabr? (My University, 2013)
Micro-abrasion tests are commonly used to perform the wear tests on hard coatings. In this study, AISI 1040 mild-steel specimens were coated with ceramic coatings including oxides with different hardness values. The free-ball micro-abrasion testing method was used to examine the wear behavior of the ceramic surfaces over different test durations. The coating-hardness measurements were carried out with a micro-hardness tester. In the experimental studies, the SiC abrasive particles with three different grain sizes (800, 1000 and 1200 mesh), were used to explore the effect of the abrasive particle size on the wear ratio of ceramic coatings. The abrasive effect of the SiC particles in the abrasive slurry was evaluated by examining the SEM micrographs of the coating surfaces. According to the test results, the sample surface coated with Cr2O3 exhibited a higher wear resistance than those covered with Al2O3 and its compositions with TiO2. It can also be concluded from the results that an increase in the percentage of the TiO2 powders in the Al2O3 mixture leads to a decrease in the wear resistance.
Keywords: Abrasive grain size; Ceramic coating; Micro-abrasion